Expression of p53 and beta-catenin proteins in hepatocellular carcinoma - Ariya, Enkhtuya; Khurelsukh, Buyanbat; Sondor, Ganbat; Ankhbayar, Enkhbaatar; Gan-Erdene, Baatarjav; Taivan, Nanzaddorj; Gantulga, Davaakhuu; Oyunsuren, Tsendsuren (Proceedings of the Institute of Biology, 2021)
The expression of p53 and beta-catenin proteins in hepatocellular carcinoma (HCC) samples with mutations in the tumor suppressor TP53 gene, which has a high frequency of mutations in liver cancer, and the CTNNB1 gene, which plays an important role in the Wnt signaling pathway, were identified. As a result, the beta-catenin protein was increased in 83.33% of liver tumor samples with CTNNB1 gene mutation, and p53 protein expression was increased in 50% of samples with TP53 gene mutation. According to this, it may be that liver tumors were caused by changes in p53 and beta-catenin protein expression. Элэгний хорт хавдрын эсийн p53, бета-катенин уургийн экспресс Элэгний хорт хавдрын мутацийн өндөр давтамжтай тохиолддог хавдар дарангуйлагч ТР53 ген болон Wnt дохиоллын замд чухал үүрэгтэй оролцдог CTNNB1 генийн мутаци илэрсэн элэгний хавдрын дээжүүдэд уургийн (p53, бета катенин) нийлэгжлийг вестерн блотын аргаар судлав. Судалгааны дүнд CTNNB1 генийн мутацитай элэгний хавдрын дээжүүдийн 83.33%-д бета-катенин уураг, ТР53 генийн мутацитай дээжүүдийн 50%-д р53 уургийн нийлэгжил тус тус нэмэгдсэн байв. Үүнээс үзэхэд p53 болон бета-катенин уургийн нийлэгжлийн өөрчлөлтөөр элэгний хавдар үүссэн байх магадлалтай. Түлхүүр үгс: мутаци, хавдар, вестерн блот